PEMANFAATAN EKSTRAK GETAH DAN KULIT BUAH MUDA TARAP (ARTOCARPUS ODORATISSIMUS) SEBAGAI LARVASIDA NABATI - Umi Latifah; Vincentia Ade Rizkya; Maria Selviana Joni; Nasrullah Tamrin; Tri Astuti Sugiyatmi (SINERGI : Jurnal Riset Ilmiah, 2026)
Dengue hemorrhagic fever (DHF) remains a major public health problem in Indonesia, highlighting the need for effective and environmentally friendly vector control strategies. Botanical larvicides derived from local plants offer a promising alternative to synthetic insecticides. This study evaluated the larvicidal activity of young tarap (Artocarpus odoratissimus) fruit sap and peel extracts against mosquito larvae. Six treatment groups were used: negative control, positive control, peel filtrate, sap filtrate, peel powder, and peel sediment, with 25 larvae per group and three replicates. Larval mortality was recorded after 24 and 48 hours. The positive control caused 100% mortality at both observation times. Among the botanical treatments, peel filtrate showed 95% mortality at 24 hours and 100% at 48 hours, while peel powder and peel sediment achieved 99–100% mortality after 48 hours. Sap filtrate produced lower but substantial mortality (89% at 48 hours). These findings indicate that young tarap fruit peel exhibits strong larvicidal activity and has considerable potential for development as an eco-friendly botanical larvicide for dengue vector control.